ENT surgical emergencies during the COVID-19 outbreak - Pontillo, Vito (Acta Otorhinolaryngol Ital, 2021)
INTRODUCTION: The restrictive measures adopted by the Italian Government during the COVID-19 outbreak caused dramatic changes in routine public health care. Surprisingly, emergency activity also registered a reduction in frequency. METHODS: This multicentre retrospective study aims to investigate eventual changes in ENT surgical emergencies in a highly populated area of southern Italy during the COVID-19 pandemic. Data concerning the period between the February 1 and the May 31, 2020 were collected from the main three hospitals in the district and compared with the same period of 2019. RESULTS: A substantial reduction was found in the number of ENT emergency interventions in 2020 compared to the same period of 2019, particularly in the main lockdown phase and in the tertiary referral centre. CONCLUSIONS: The reduction in the absolute number of emergency ENT interventions can be only partially explained by social distancing and home confinement. We have reason to believe that some of these patients may have not sought medical support due to fear of nosocomial SARS-CoV2 infection. This study could represent a trigger for further implementation of health system responses to emergencies in a period of transition that is likely to last for a prolonged period of time.